Kesehatan Lingkungan Udara Ruang Rawat Inap Rumah Sakit Syekh Yusuf Kabupaten Gowa - Lisa Jayanti; Syamsuar Manyullei; Emmi Bujawati (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
The hospital is a place where ill people are treated and placed in a very close distance. In this place patients receive therapy and treatment to recover. Hospital is not only a place to get recovered but also a depot for various diseases that come from the patient or from a visitor who is a carrier. Germs can live and thrive in hospital environment covering the whole area, like air, water, flooring, food and both medical and non medical. The purpose of this study was to determine the factors that influence the quality object of inpatient room sanitation of District General Hospital with an exposure Sheikh Yusuf room temperature, humidity, inspection and measurement number of bacteria PM2,5 and PM10 dust particles. This is a descriptive research with 5 types room of population and two rooms of sample in Syekh Yusuf regional hospital. The result of the exposure/lighting measurement both treatment room I and II are not eligible and the humadity is not either as well germs measurement. The measurements of dust particle PM2,5 and PM10 in both treatment room I and II is eligble based on the decree of health ministry of RI number 1204/Menkes/SK/2004 regarding with condition of hospitasl environment health. Therefore, it is to advisible that hospital does room cleaning process on a regular basis in inpatient room.Keywords : lighting, room temperature, room humidity, Figures Germs, dust and PM10 PM2,5